Analyzing The Behavior of Classical Functionally Graded Coated Beam - Toudehdehghan, Abdolreza*; Rahman, M. M.; Tarlochan, F. (EDP Sciences, 2017)
The governing equation of a classical rectangular coated beam made of two homogeneous layers at top ceramic coated layer and bottom metal layer and also single Functionally Graded Material (FGM) as a sub coated layer subjected to uniform distributed mechanical load are derived by using principle of virtual displacements and based on Euler-Bernoulli deformation beam theory (EBT). In FGM layer the material properties are presumed differ as an exponential function form in thickness coordinate. Hence, the aim of this paper is analyzed the static behavior of clamped-clamped thin coated beam under mechanical load.